On lacunary weak statistical convergence of order ? - Ercan, Sinan; Altin, Yavuz; Bektas, Cigdem A. (Taylor & Francis Inc, 2020)
In this paper, we introduce lacunary weak statistical convergence of order alpha and weak -convergence for . We prove some properties of these modes of convergence and give some inclusion relations.
Keywords: Statistical convergence; weak convergence; lacunary sequence